Safety climate as a risk factor of occupational accidents in a textile industry - Karlina Wirawati; Ardini Raksanagara; Sharon Gondodiputro; Deni K Sunjaya; Hadyana Sukandar; Sri Yusnita Irdasari (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
Purpose: This study aimed to analyze several risk factors of safety climate e.g. management safety priority and commitment, management safety empowerment, management safety justice, workers’ safety commitment, workers’ safety priority, safety in learning, communication, and innovation, and worker’s trust in the efficacy of safety system with occupational accidents in a spinning.Methods: This case-control study involved 120 workers divided into two groups, the control group (80 subjects) and the case group (40 subjects). The case group consisted of spinning workers who had experienced occupational accidents in the last two years in the textile industry in Bandung. The bivariate analysis uses a chi-squared, while multivariable analysis with multiple logistic regression.Results: The results show that PPE use and management safety empowerment influenced occupational safety, becoming a risk factor for occupational accidents. Management safety empowerment was considered the primary factor of occupational accidents with an adjusted odds ratio of 5.52 (CI 95% 2.26–13.44).Conclusions: Management safety empowerment that influenced occupational safety programs can improve social exchanges and support workplace safety to encourage occupational safety behavior.